The auroral radio emission of the magnetic B-type star ρ OphC. (10th September 2020) - Leto, P; Trigilio, C; Buemi, C S; Leone, F; Pillitteri, I; Fossati, L; Cavallaro, F; Oskinova, L M; Ignace, R; Krtička, J; Umana, G; Catanzaro, G; et al.
ABSTRACT: The non-thermal radio emission of main-sequence early-type stars is a signature of stellar magnetism. We present multiwavelength (1.6–16.7 GHz) ATCA measurements of the early-type magnetic star ρ OphC, which is a flat-spectrum non-thermal radio source. The ρ OphC radio emission is partially circularly polarized with a steep spectral dependence: the fraction of polarized emission is about $60{{\ \rm per\ cent}}$ at the lowest frequency sub-band (1.6 GHz) while is undetected at 16.7 GHz. This is clear evidence of coherent Auroral Radio Emission (ARE) from the ρ OphC magnetosphere. Interestingly, the detection of the ρ OphC's ARE is not related to a peculiar rotational phase. This is a consequence of the stellar geometry, which makes the strongly anisotropic radiation beam of the amplified radiation always pointed towards Earth. The circular polarization sign evidences mainly amplification of the ordinary mode of the electromagnetic wave, consistent with a maser amplification occurring within dense regions. This is indirect evidence of the plasma evaporation from the polar caps, a phenomenon responsible for the thermal X-ray aurorae. ρ OphC is not the first early-type magnetic star showing the O-mode dominated ARE but is the first star with the ARE always on view.